Digital assessment of cognition in neurodegenerative disease: a data driven approach leveraging artificial intelligence - Libon, David J.; Swenson, Rod; Price, Catherine C.; Lamar, Melissa; Cosentino, Stephanie; Bezdicek, Ondrej; Kling, Mitchel A.; Tobyne, Sean; Jannati, Ali; Banks, Russell; Pascual-Leone, Alvaro (Frontiers in Psychology, 2024)
Pascual-Leone, and Jannati are listed as inventors on a pending patent assessing central nervous system functionality using a digital tablet and stylus. Dr. Pascual-Leone serves as a paid member of the scientific advisory boards for Neuroelectrics, Magstim Inc., TetraNeuron, Skin2Neuron, MedRhythms, and Hearts Radiant. He is a co-founder of TI Solutions and co-founder and chief medical officer of Linus Health and receives shares or share options from Linus Health. Dr. Pascual-Leone is listed as an inventor on several issued and pending patents on the real-time integration of transcranial